Female entrepreneurship : an exploratory study of women entrepreneurs in Ireland - Humbert, Anne Laure (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2007)
This thesis consists of an exploratory study of female entrepreneurship in Ireland, focusing on the motivations, obstacles and work/life balance experiences of entrepreneurs. The research relies on a combination of quantitative and qualitative methods to answer the research questions. A postal questionnaire was sent to entrepreneurs nationally and offered a comparative perspective between men and women entrepreneurs on entrepreneurial motivations, obstacles encountered, levels of risks adopted and attitudes to work/life balance. Due to the nature of the research question, the quantitative data was complemented by a series often interviews with women entrepreneurs. The interviews further explored the issues raised by the questionnaires. Particular interest was given to the motivational factors of women entrepreneurs, to the obstacles they encountered, and to their attitudes to risk. Women entrepreneurs' attitudes to work/life balance practices and the relationship between this and the level of conflict between their work and family life were also explored.
Keywords: Statistics, Ph.D.; Ph.D. Trinity College Dublin